African Women and Peace Building - Dagogo, Doctor Farah (International Journal on Economics, Finance and Sustainable Development, 2022)
The role of women in peace building in Africa has inspired a lot of literature in contemporary times. Therefore, this paper examines the role of African women in peace building effort in Africa. The paper review related literature on peace building especially in African perspective. The paper was guided by the Radical Feminism theory, and historical method was used as its research design. The secondary data gathered were thoroughly subjected to content analysis. The paper revealed some of the major challenges confronting African women in peace-building as: lack of political strength and political vision, lack of experience, exposure and skills in negotiation, advocacy and lobbying techniques, lack of resources (material and financial) and lack of sustainability in political participation. The foregoing realities point to the fat that African women are largely disadvantaged when it comes to peace building in the continent. The implication of this is that woman has largely been excluded from the peace building process in most of the Africa States. This artificial barriers inhibited women from peace building effort in African continent and Nigeria in particular. Therefore, the paper recommended among other things that Peace building activities in Africa need to support women’s group and local initiatives in their own capacities, by seeing women as untapped resources and dynamic elements of post-conflict societies in Africa.